Cadmium concentration and genetic polymorphism of GSTM1, GSTP1 and GSTT1 in blood samples of respondents from Melaka, Malaysia - Md Zulkifli, Hamizah (2018)
Eating seafood has become a major health concern for many people due to the present of the heavy metal especially cadmium (Cd) in that source of protein. Cd can accumulate in the body and disrupt the normal cellular processes which will eventually lead to organ damage. Due to the different of genetic composition of an individual, the amount of Cd accumulates in the body is different from each other even though they consume almost the same kind of food in everyday lives. This showed that the allele differences or specifically genetic polymorphism might probably exist in one or more human genes (GSTM1, GSTT1 and GSTP1) which related to Cd detoxification. This study was conducted to determine the association between frequency intake of ten most consumed seafood and seafood products with blood Cd level and to determine the association between blood Cd level with genetic polymorphism of GSTM1, GSTP1 and GSTT1 among respondents in Malacca. A total of 403 respondents were recruited in this study and were given a set of questionnaire to gather information about seafood frequency intake and background information of potential exposure to Cd. Blood samples of 63 respondents were taken and analyzed by using ICP-MS. DNA from the blood samples were extracted and analyzed by using PCR and PCR RFLP to determine the presence and absent of polymorphisms in those genes. The most common seafood and its product that were frequently consumed by the respondents were shrimp paste (31.5%) followed by mackerel (13.6%), hardtail-scad (6.2%), flatfish (4.5%), fish ball (4.0%), fish crackers (2.2%), shrimp ball (2.2%), squid (2.2%), crab ball (2.2%), and wolf herring (2.0%). All the 63 blood samples showed the present of Cd with the median concentration of 0.076μg/L (IQR=0.1) and range between 0.007 μg/L to 1.284 μg/L. The median does not exceeded the permitted value stated by Agency for Toxic Substances and Disease Registry (ATSDR) which is 0.315 μg/L. There were 40 (63.5%) of the respondents having the GSTM1 null genotype (polymorphism) while for GSTT1 gene, there were 24 (38%) of them having GSTT1 null genotype (polymorphism). For the GSTP1 gene, there were in total of 35 (55.6%) of the respondents having GSTP1 polymorphism in their body. No association was observed between frequency intake of 10 mostly consumed seafood and seafood products with blood Cd level of the respondents. There was also no association found between blood Cd level and polymorphism of GSTM1, GSTT1 and GSTP1. However, GSTM1 and GSTP1 genes showed some trends in which the respondents with no polymorphism (wildtype) were having higher median of blood Cd level compared to those who were polymorphic. Seafood and seafood products consumption were not significantly associated with the blood Cd level. Although blood Cd level was found to be not significantly associated with the polymorphism of those three genes, the trends observed during analysis showed that polymorphism of GSTM1 and GSTP1 may increased the efficiency of Cd to be secreted out of the body. Larger sample size is needed to further confirm the association between those two variables.